Prediction of Single Sphere Motion in Newtonian and Non-Newtonian State Fluids (University of Khartoum Engineering Journal, 2022)
The motion of particles such as spheres immersed in fluids represents an idealization of various industrial processes. Such as, sedimentation and fluidized suspensions, lubricated transport, or general unit operation processes. The motion of spheres falling through static fluids was studied. The objective was to study the different flow patterns and to predict the terminal falling velocity and drag coefficient of particles settling in Newtonian and non-Newtonian (shear-thinning) fluids. The velocity of a falling sphere was measured as a function of time and sphere density. Particles of different sizes and densities, beside different types of fluids such as engine oil, glycerine, and kerosene representing non-Newtonian (shear-thinning)] were used. Derived experimental data for solid spheres falling through Newtonian and non-Newtonian fluids were reported, using fluid properties and hydrostatics bench apparatus. Empirical equations were formulated and developed for predicting drag coefficient and terminal falling velocity of solid spheres falling through stagnant fluids.